You'll never walk alone: Unemployment, social networks and leisure activities - Mattia Filomena; Matteo Picchio (Global Labor Organization (GLO), 2023)
We analyse how unemployment affects individuals' social networks, leisure activities, and the related satisfaction measures. Using the LISS panel, a representative longitudinal survey of the Dutch population, we estimate the effects by inverse propensity score weighting in a difference-in-differences design in order to deal with unobserved heterogeneity and unbalanced covariate distribution between treated and control units potentially associated with the dynamics of the outcome variables. We find that, after job loss, individuals increase their network size by strengthening their closest contacts within the family, spending more time with neighbors, and making more use of social media. Although they devote their extra leisure time mostly to private activities, our results do not support the hypothesis of social exclusion following unemployment.
Keywords: I31; J01; J64; 330; Unemployment; job loss; social exclusion; leisure; social satisfaction; doubly robust difference-in-differences